Narrow Leaf21, encoding ribosomal protein RPS3A, controls leaf development in rice. Issue 1 (16th February 2021) - Uzair, Muhammad; Long, Haixin; Zafar, Syed Adeel; Patil, Suyash B; Chun, Yan; Li, Lu; Fang, Jingjing; Zhao, Jinfeng; Peng, Lixiang; Yuan, Shoujiang; Li, Xueyong
Abstract : A ribosomal protein controls rice leaf width through translational regulation of auxin response factors and a key transcription factor regulating blade lateral outgrowth. Abstract: Leaf morphology influences photosynthesis, transpiration, and ultimately crop yield. However, the molecular mechanism of leaf development is still not fully understood. Here, we identified and characterized the n arrow l eaf21 ( nal21 ) mutant in rice ( Oryza sativa ), showing a significant reduction in leaf width, leaf length and plant height, and increased tiller number. Microscopic observation revealed defects in the vascular system and reduced epidermal cell size and number in the nal21 leaf blade. Map-based cloning revealed that NAL21 encodes a ribosomal small subunit protein RPS3A. Ribosome-targeting antibiotics resistance assay and ribosome profiling showed a significant reduction in the free 40S ribosome subunit in the nal21 mutant. The nal21 mutant showed aberrant auxin responses in which multiple auxin response factors (ARFs) harboring upstream open-reading frames (uORFs) in their 5′-untranslated region were repressed at the translational level. The WUSCHEL-related homeobox 3A ( OsWOX3A ) gene, a key transcription factor involved in leaf blade lateral outgrowth, is also under the translational regulation by RPS3A. Transformation with modified OsARF11, OsARF16, and OsWOX3A genomic DNA (gDNA) lacking uORFs rescued the narrow leaf phenotype of nal21 to a better extent than transformation with their native gDNA, implying that RPS3A could regulate translation of ARFs and WOX3A through uORFs. Our results demonstrate that proper translational regulation of key factors involved in leaf development is essential to maintain normal leaf morphology.